Melamine-Assisted Thermal Activation Method for Vacancy-Rich ZnO: Calcination Effects on Microstructure and Photocatalytic Properties - Weiwei Wang; Lin Lv; Changfeng Wang; Jiao Li (Molecules, 2023)
Defect engineering is considered an effective method to adjust the photocatalytic properties of materials. In this work, we synthesized the vacancy-rich ZnO rods with (100) planes via the melamine-assisted thermal activation method. A high concentration of oxygen vacancies was successfully introduced into non-polar oriented ZnO rods by calcination. The effect of oxygen vacancy on the photocatalytic properties of non-polar-oriented ZnO rods was investigated. Raman and XPS spectra revealed the formation of oxygen vacancies in the ZnO. The results showed that the growth habit and defects in ZnO can be controlled by changing the ratio of ZnO to melamine. The higher ratio of ZnO to melamine led to more amounts of (100) planes and oxygen vacancies in ZnO, and it reached the highest when the ratio was 1.2:1. When the ratio was 1.2:1, ZnO exhibited a high methyl orange degradation rate (95.8%). The differences in oxygen vacancy concentration and non-polar planes were responsible for the improvement in photocatalytic performance. ZnO exhibited good stability and regeneration capacity. After recycling four times, the degradation rate was still at 92%. Using the same method, vacancy-rich α-Fe2O3 was obtained. This work could offer a new and simple strategy for designing a photocatalyst with oxygen vacancies.